The Effect of Patients' Perceptions on the Quality of Health Services on the Reuse of Health Services in the Work Area of the Health Services of West Langsa - Nur Anifah; Asyiah Simanjorang; Yuniati Yuniati (Journal La Medihealtico, 2021)
The purpose of the study was to determine and analyze the effect of perceptions of responsiveness, reliability, assurance, empathy, tangible and dominant factors on the reuse of health services in the work area of Langsa Health Center. West. The research method uses an analytical survey with a cross sectional approach. The population in the study was 5.5362 people. The sampling technique used the Slovin formula and accidental sampling, so that 99 people were obtained. Data analysis used univariate, bivariate with chi-square test and multivariate with logistic regression test. The results showed that the multivariate sig value of perceived responsiveness (0.000), perceived reliability (0.214), perceived assurance (0.040), perception of empathy (0.017), perception of real evidence (0.195). The conclusion is that there is an influence of perception of responsiveness, assurance, empathy, there is no influence of perception of reliability and direct evidence on the reuse of health services, while the dominant factor of reuse of health services is the perception of responsiveness. For this reason, it is recommended for the Puskesmas to further improve the quality of its services related to communication of doctors' schedules so that they come on schedule, explain the provisions on the use of generic drugs for JKN patients, and doctors use the principles of smile, greet and touch to serve patients.